(untitled) (Research, Society and Development, 2021)
Objectives: To verify the number of visceral leishmaniasis (VL) cases in Brazil and its states and twin cities, with a focus on the state and twin city with the highest number of cases. We investigated social, demographic, laboratory and clinical aspects of these cases. Methodological design: We performed a descriptive study using a quantitative approach and data from 2010 to 2019 that were obtained through a public domain website, the Informatics Department of the Unified Health System. The incidence rate of VL cases was calculated per 100,000 inhabitants. software. Results: In Brazil, 35,886 VL cases were reported, with 2,834 cases in international border states and 148 cases in twin cities. The state and twin city with the highest number of cases were Mato Grosso do Sul (1,834 cases) and Corumbá (94 cases), respectively, with annual mean incidence rates of 6.4 and 8.3 cases per 100,000 inhabitants. In Mato Grosso do Sul and Corumbá, the disease was more frequent in male and brown-skinned individuals who had up to 8 years of education (age range: 1 to > 80 years old). Most of the cases occurred in urban areas, was diagnosed by laboratory tests and evolved to cure (p < 0.05). Conclusions: A high number of VL cases in Brazil was found during the period of study. The cases were distributed in 10 states with international borders and eight twin cities. These findings draw attention to the greater need for management programs to control and prevent VL.